2007
DOI: 10.1161/hypertensionaha.107.094987
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Mas-Mediated Bradykinin Potentiation by the Angiotensin-(1-7) Nonpeptide Mimic AVE 0991 in Normotensive Rats

Abstract: Abstract-We evaluated the effect of the nonpeptide mimic of angiotensin (Ang)-(1-7), AVE 0991, on the hypotensive effect of bradykinin (BK). Increasing doses of intra-arterial or intravenous BK were administered before and 30 minutes after the beginning of AVE 0991 infusion. The effect of AVE 0991 on plasma Ang-converting enzyme activity was tested using Hip-His-Leu as the substrate. The interaction of AVE 0991 with Ang-converting enzyme in vivo was tested by determining its effect on the pressor action of Ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 38 publications
(54 reference statements)
1
28
0
Order By: Relevance
“…Although, the intracellular pathway coupling Ang-(1-7) stimulation is incompletely characterized, it has been reported that an important subset of cardiovascular actions of Ang-(1-7) is related to its BK potentiating activity and its facilitation of NO release [Brosnihan et al 1996; Pinheiro et al 2004; Wiemer et al 2002; Yuill et al 2010]. Mas receptors localized to cardiac myocytes may activate NO production or stimulate BK [Almeida et al 2000; Carvalho et al 2007; Ferreira et al 2001]. Consistent with previous studies, we observed the involvement of the NO and BK pathways in the altered I Ca , L response to Ang-(1-7) in HF.…”
Section: Discussionmentioning
confidence: 99%
“…Although, the intracellular pathway coupling Ang-(1-7) stimulation is incompletely characterized, it has been reported that an important subset of cardiovascular actions of Ang-(1-7) is related to its BK potentiating activity and its facilitation of NO release [Brosnihan et al 1996; Pinheiro et al 2004; Wiemer et al 2002; Yuill et al 2010]. Mas receptors localized to cardiac myocytes may activate NO production or stimulate BK [Almeida et al 2000; Carvalho et al 2007; Ferreira et al 2001]. Consistent with previous studies, we observed the involvement of the NO and BK pathways in the altered I Ca , L response to Ang-(1-7) in HF.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the mechanism of aerobic exercise training to prevent LVH could occur by diminished vascular resistance leading to increased cardiac flow, due to the reduction in ACE and Ang II levels and the vasodilator effects of the ACE2-Ang (1–7) expression, mediating the release of different vasoactive factors such as nitric oxide, prostaglandins and bradykinin (40,41). …”
Section: Discussionmentioning
confidence: 99%
“…22,23 Rats whose Mas gene was knocked out showed few reactions and beneficial effects when given Ang- (1-7). 24,25 Therefore, connected by Ang- (1-7), a functional axis of ACE2-Ang-(1-7)-Mas was formed. As we know from many past studies about other members of RAS, such as angiotensinogen, renin, Ang II and ACE, inter-regulations between components of RAS are quite common.…”
Section: Discussionmentioning
confidence: 99%